2021
DOI: 10.3390/cancers13040602
|View full text |Cite
|
Sign up to set email alerts
|

The Perspectives of Fertility Preservation in Women with Endometrial Cancer

Abstract: Endometrial cancer is the most common gynecological cancer in developed countries. The disease is diagnosed with increasing frequency in younger women, commonly also in their reproductive age. The standard treatment of endometrial cancer is surgical in the form of hysterectomy and bilateral salpingo-oophorectomy, and this precludes future fertility in younger women. The current challenge is to identify the group of women with endometrial cancer and low-risk features that would benefit from more conservative tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 78 publications
0
26
0
Order By: Relevance
“…Synchronous or metastatic ovarian cancer occurs in 5–29% of patients with endometrial carcinoma, and younger women <45 years of age are five times more likely to have synchronous ovarian cancer than women aged >45 years ( Obermair et al , 2020 ). However, in women with low-risk disease (no myometrial invasion, Grade 1 endometrioid histology, normal looking ovaries) no cases of ovarian cancer were detected ( Knez et al , 2021 ). Adnexal involvement can be identified using pelvic MRI or transvaginal US ( Guillon et al , 2019 ; Obermair et al , 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Synchronous or metastatic ovarian cancer occurs in 5–29% of patients with endometrial carcinoma, and younger women <45 years of age are five times more likely to have synchronous ovarian cancer than women aged >45 years ( Obermair et al , 2020 ). However, in women with low-risk disease (no myometrial invasion, Grade 1 endometrioid histology, normal looking ovaries) no cases of ovarian cancer were detected ( Knez et al , 2021 ). Adnexal involvement can be identified using pelvic MRI or transvaginal US ( Guillon et al , 2019 ; Obermair et al , 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…With an increasing incidence of EC in younger women, increasingly more women are likely to seek conservative management options to preserve their uterus. Fertility-sparing management is well known and has been used for young women with EC and AEH who wish to preserve their fertility (12). Previous studies revealed a high remission rate of conservative treatment, as well as an association with a high rate of relapse, ranging from 10% to 88%, which is the most problematic feature of this therapy (13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Of 80 patients who received repeated conservative treatment after relapse, 71 (88.6%) patients achieved CR with the 6 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) months' median CR time. Seven (8.8%) patients failed to achieve CR, one PR, four SD, and two PD and then underwent hysterectomy with or without lymphadenectomy (Figure 1).…”
Section: Treatment Outcomes Of the First Fertility-sparing Re-treatmentmentioning
confidence: 99%
“…Side-effects or contraindications of progestins, such as weight gain or liver dysfunction call for alternative regimes other than oral high dose progestins. (12) .…”
Section: Discussionmentioning
confidence: 99%